Identificação de sistemas em motores de indução trifásicos - Borges, Daniel Tobias da Silva (2016)
In the present scenario rotating machines have been widely used in industry because of its relative simplicity, constructive robustness and low price. In this context, adequately characterize engine behavior in nominal operating conditions, as this mathematical modeling of these machines becomes interesting and can contribute to the implementation of a predictive control real-time, moreover, there fault detection possibility to, since the engine behavior change will be felt by the identified model. One way to get this mathematical structure is through their experimental data input and output, in order to identify systems is a good option as it studies ways to model and analyze systems, through its information input and output, with the aim of discovering knowledge standards. In this context, the work is to develop a mathematical model using system identification techniques in three phase induction machines through the experimental data with the objective to implement a model apt to behavior anticipate the three-phase induction motor application control for prediction. Moreover, it presents the importance of modeling the rotating machine, moreover, is demonstrated using the method of modeling identification system and a brief justification about ARX and ARMAX models. Also there was performed parametric estimation and then we performed a test to show the performance of the identification of the three-phase induction motor.